Optical spectra of FO Aquarii during low and high accretion rates. Issue 4 (23rd May 2020) - Kennedy, M R; Garnavich, P M; Littlefield, C; Marsh, T R; Callanan, P; Breton, R P; Augusteijn, T; Wagner, R M; Ashley, R P; Neric, M
ABSTRACT: Between 2016 May and 2018 September, the intermediate polar (IP) FO Aquarii exhibited two distinct low states and one failed low state. We present optical spectroscopy of FO Aquarii throughout this period, making this the first detailed study of an accretion disc during a low state in any IP. Analysis of these data confirm that the low states are the result of a drop in the mass transfer rate between the secondary star and the magnetic white dwarf primary, and are characterized by a decrease in the system's brightness coupled with a change of the system's accretion structures from an accretion disc-fed geometry to a combination of disc-fed and ballistic stream-fed accretion, and that effects from accretion on to both magnetic poles become detectable. The failed low state only displays a decrease in brightness, with the accretion geometry remaining primarily disc-fed. We also find that the WD appears to be exclusively accretion disc-fed during the high state. There is evidence for an outflow close to the impact region between the ballistic stream and the disc which is detectable in all of the states. Finally, there is marginal evidence for narrow high-velocity features in the H α emission line during the low states which may arise due to an outflow from the WD. These features may be evidence of a collimated jet, a long predicted yet elusive feature of cataclysmic variables.